Letter: stepwise diagnosis in covert hepatic encephalopathy – critical flicker frequency and MELD‐score as a first‐step approach. Replication and pitfalls. Authors' reply. Issue 1 (2nd December 2016) - Greinert, R.; Zipprich, A.; Ripoll, C.
Abstract : Linked Content This article is linked to Greinert et al and Zacharias et al papers. To view these articles visithttps://doi.org/10.1111/apt.13721 andhttps://doi.org/10.1111/apt.13830 .